Evaluación de impacto ambiental en obras de construcción del barranco tumino de la ciudad de Moyobamba - Zapata Vela, Cronwell Macoy (2015)
This thesis research project is to make an assessment of the environmental baseline -that Tumino ravine Moyobamba, the same has become the focus ofthe May high and the department of San Martin is located due to the implementation of a large number of activities that have been implemented year after year construction works in Barranco Tumino of Moyobamba. The current municipal government has every interest to address issues related to the development of basic infrastructure Urbana, in that sense, 1 urge me to have to do this research for the . purpose of improving the urban and pedestrian urban area of the city of Moyobamba and promptly to gradually improving walkability in the neighborhood of Zaragoza, Huastilla sector, it helps improve the conditions of life of the main often make use of such services in urban areas and green areas and natural ecosystems in the case of the Canyons. The purpose of this research is to develop the Environmental lmpact Study for the construction of Barranco Tumino of Moyobamba, also, allows handle adequately the potential negative impacts of construction activities products that can be generated in different stages of the project cycle. lt is important that you begin to display more seriously the public need for urban canyons and natural ecosystems are properly sanitized and provide additional services to the community.